Characterization of mudejar mortars from St. Gil Abbot church (Zaragoza, Spain): Investigation of the manufacturing technology of ancient gypsum mortars - Igea, J.; Lapuente, P.; Martínez-Ramírez, S.; Blanco-Varela, M. T. (Materiales de Construcción, 2012)
This work has been focused on the investigation of the technological procedure of Mudejar mortars applied to the characterization of a group of unaltered samples from an example church of Mudejar architecture of Aragon. The research was carried out using multi-analytical techniques including petrographic study, chemistry and mineralogical analysis. All mortars present a homogeneous composition. The binder is made up of a mixture of gypsum and a very low proportion of lime, while the main components of the aggregate are gypsum and carbonate rock fragments, both in a different thermal state of decomposition. The results have proved that both, binder and aggregates display the same composition in these mortars. These aggregates are the by-product of a grinding process of the previously burnt raw materials which have had a positive influence on the properties of the mortars in improving their quality.